Grain boundary-constrained reverse austenite transformation in nanostructured Fe alloy: Model and application. (1st August 2018) - Huang, Linke; Lin, Weitong; Wang, Kang; Song, Shaojie; Guo, Can; Chen, Yuzeng; Li, Yujiao; Liu, Feng
Abstract: Reverse austenite transformation (RAT) is critical for designing advanced high-strength steels (AHSS), which, however, has not been sufficiently studied in nanostructured (NS) steels or Fe alloys, and hence not fully understood yet. Herein, the RAT (e.g. ferrite to austenite) kinetics in the NS Fe alloy upon continuous heating was experimentally and theoretically investigated, where, the ultrafine austenite characterized by a sluggish growth velocity and a high thermal stability, and additionally, an appreciable solute partitioning detected using atom probe microscopy, indicate the diffusion-controlled mechanism of RAT. The double-edged role of grain boundaries (GBs) in the NS alloy is elucidated, i.e. enhancing the diffusivity due to the type-A kinetics, and simultaneously, facilitating the formation of constrained diffusion field mainly due to the segmented effect of GB nucleation. On this basis, a modified diffusion model incorporating the effect of GBs is implemented to understand the GB-constrained austenite growth and the associated partitioning behavior, and further complemented with Cahn model, an austenite growth model is applied to predict the overall kinetics of RAT in the NS Fe alloy. It then follows that a strategy by combination of diffusion-controlled growth model and microstructure model could serve as a framework to predict the kinetics of RAT in the NS alloys. Regarding the RAT kinetics in the NS alloys, the present work uncovers the 'GB-constrained' mechanism, which is expected to offer the potential application for nanostructure manipulation in the development of AHSS. Graphical abstract: Image 1